Analysis of Business Growth of Batik MSMEs in the Covid-19 Pandemic - Rina Rachmawati; Sicilia Sawitri; Musdalifah Musdalifah; Wulansari Prasetyaningtyas (Publindo Akademika, 2022)
The rapid spread of the Covid-19 virus to various parts of the world has an impact on the world economy, both in terms of trade, tourism and investment. Small and Medium Enterprises (MSMEs) have felt the significant impact of Covid-19. The batik industry is also affected because it involves imported raw materials, although there are some batik industries that can escape the hustle and bustle of the impact of Covid-19 and are able to experience business growth. This study will analyze the business growth of batik SMEs, especially Kauman Pekalongan batik and the factors that influence business growth are business management. The purpose of this research is on the growth conditions of the Pekalongan Batik MSME business during the Covid-19 pandemic. This study uses a grand theory, namely the theory of finance and the theory of entrepreneurship. The results showed that there was a decrease in operating income, a sluggish batik market from both the consumer and business perspective, difficulty in distributing raw materials and rising material prices which caused several businesses to close and shift their business lines. The analysis showed that 47% of the business growth of Batik SMEs in Pekalongan is influenced by business management which consists of business financial management, production management, entrepreneurial characteristics and digital technology. The limitations of the study due to social curbs which made it difficult to access research data had an impact on the time of the study.